Angular-Resolved Magnetometry Beyond Triclinic Crystals: Out-of-Equilibrium Studies of Cp*ErCOT Single-Molecule Magnet - Boulon, Marie-Emmanuelle (WILEY-V C H VERLAG GMBH, 2022)
10.1002/chem.201302600